2018
DOI: 10.1007/s42452-018-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CeO2 on the microstructure and properties of 2A12 porous aluminum

Abstract: The micron porous aluminum has received considerable attention in various domains, and the research of rare earths for the synthesis of materials with improved mechanical performance. In the present work, 2A12 aluminum alloys with different porosities were successfully prepared by cold pressing-vacuum sintering-dissolution process (SDP) with the CeO 2 additive, and the CeO 2 content effect on the microstructure and mechanical properties of the porous aluminum alloys were investigated. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Taguchi method can be used to investigate and improvise the various variables that affect the produced AMMCs' qualities. The impacts of CeO 2 on the mechanical characteristics were assessed by Chao Liu [14]. The findings demonstrated that CeO 2 caused an enhancement in the mechanical characteristics of Al alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Taguchi method can be used to investigate and improvise the various variables that affect the produced AMMCs' qualities. The impacts of CeO 2 on the mechanical characteristics were assessed by Chao Liu [14]. The findings demonstrated that CeO 2 caused an enhancement in the mechanical characteristics of Al alloys.…”
Section: Introductionmentioning
confidence: 99%
“…% of CeO 2 increased the tensile strength of the MMCs. Chao Liu et al [11] evaluated the effects of CeO 2 on the mechanical behavior. The outcomes showed that the presence of CeO 2 led to enhancement in the mechanical behavior of the Al alloys.…”
Section: Introductionmentioning
confidence: 99%